2005
DOI: 10.1152/jn.00533.2004
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Spatial and Temporal Coding by Semicircular Canal Afferents

Abstract: . Determinants of spatial and temporal coding by semicircular canal afferents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 88 publications
3
48
0
Order By: Relevance
“…Therefore, the membrane has to be replaced regularly and T c must be determined before every experiment. The calibration test makes use of the well-known phenomenon (Grant and Van Buskirk, 1976;Highstein et al, 2005) that a deflected cupula in a SCC at rest relaxes according to (7) y c ∼ e −t/Tc .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the membrane has to be replaced regularly and T c must be determined before every experiment. The calibration test makes use of the well-known phenomenon (Grant and Van Buskirk, 1976;Highstein et al, 2005) that a deflected cupula in a SCC at rest relaxes according to (7) y c ∼ e −t/Tc .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown a strong inverse correlation between the sensitivity at the spike-initiation site of vestibular-nerve afferents and their regularity of background discharge rate (Goldberg et al 1984;Baird et al 1988;Highstein et al 2005). This post-synaptic gain has been shown in the chinchilla to be at least an order of magnitude greater in "calyx-only" afferents than in afferents that are more regularly discharging (Baird et al 1988).…”
Section: Responses At 2 Hzmentioning
confidence: 99%
“…Despite the co-variation between response dynamics and regularity, it is generally argued that they arise from distinct mechanisms. Variation in response dynamics is attributed to mechanical factors, affecting the input to hair cell transduction channels and hair cell processes (for a review, see Eatock and Lysaksowski, 2006), which may include synaptic mechanisms (Highstein et al, 2005). As we shall discuss, factors determining firing regularity are held to be postsynaptic, with speculation centered on the morphology of afferent dendrites and on ion channels (Highstein and Politoff, 1978;Smith and Goldberg, 1986) (for a review, see Goldberg, 2000).…”
Section: Firing Regularitymentioning
confidence: 99%